2007
DOI: 10.1016/j.nurt.2007.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Episodic Ataxia Type 2

Abstract: Summary: Episodic ataxia type 2 (EA 2) is a rare neurological disorder of autosomal dominant inheritance resulting from dysfunction of a voltage-gated calcium channel. It manifests with recurrent disabling attacks of imbalance, vertigo, and ataxia, and can be provoked by physical exertion or emotional stress. In the spell-free interval, patients present with central ocular motor dysfunction, mainly downbeat nystagmus. A slow progression of cerebellar signs accompanied by a slight atrophy of midline cerebellar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
96
1
18

Year Published

2007
2007
2017
2017

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 162 publications
(117 citation statements)
references
References 67 publications
2
96
1
18
Order By: Relevance
“…• Episodic ataxia type 2: the duration of the attacks varies from several minutes to hours and more than 90% of the patients have cerebellar signs, in particular gaze-evoked nystagmus and downbeat nystagmus [20,40]. The onset of manifestations after the age of 20 is unusual.…”
Section: Differential Diagnosismentioning
confidence: 99%
“…• Episodic ataxia type 2: the duration of the attacks varies from several minutes to hours and more than 90% of the patients have cerebellar signs, in particular gaze-evoked nystagmus and downbeat nystagmus [20,40]. The onset of manifestations after the age of 20 is unusual.…”
Section: Differential Diagnosismentioning
confidence: 99%
“…In humans, mutations in the CACNA1A gene cause, in addition to FHM1, a few autosomal dominant neurological disorders characterized by cerebellar dysfunction, such as episodic ataxia type 2 (that may be associated with absence epilepsy in a few cases) and spinocerebellar ataxia type 6 9,26,27 (compare, Strupp 28 and Gomez 29 31,35,37,38 Recently, the generation of knockin mice carrying two different FHM1 mutations (R192Q and S218L) allowed the first analysis of mutant channels expressed at their endogenous level in neurons. [39][40][41] The studies in heterologous expression systems showed that the FHM1 mutations alter many biophysical properties of human Ca V 2.1 channels, in a complex way.…”
Section: Familial Hemiplegic Migraine Type 1 (Fhm1)mentioning
confidence: 99%
“…31 These clinical signs help to differentiate patients with EA2 from patients with migraine, who only present with minor ocular motor dysfunction. 32,34 In the past, the treatment of choice was the carbonic anhydrase inhibitor acetazolamide in a dosage of 250-1,000 mg/d. 35 Acetazolamide had been shown to suppress the number and severity of attacks in EA2, and effects on interictal oculomotor and postural function have also been documented.…”
Section: Treatment Of Different Types Of Nystagmus With 4-apmentioning
confidence: 99%